Balanced Security and Humanity: an Analysis of Australian Policies in Handling of Boat People and Its Impact on Indonesia - Maria Natasha Rudijanto; Vania Clianta Putri; Ellen Santoso (Asian Journal of Social and Humanities, 2023)
The rise of Boat People arriving in Australia made the Australian government issue a policy called a policy Operation Sovereign Border, the policy is a policy used to deal with asylum seekers by preventing and expelling asylum seekers. This policy reaped controversy because it violated the provisions of international law. This legal writing analyzes how efforts to deal with boat people and their rights and obligations according to international law as well as the influence of Australian policies in dealing with boat people and the impact of Australian policies on Indonesia. This research uses a normative juridical method which is carried out through a literature study with a statutory, historical approach, and conceptual. Australia has also ratified the 1951 Convention which has become the basis of international law for refugees, and has also regulated the protection of refugees and has become a reference for many countries in developing their refugee laws and policies. Australia's policy on preventing migration by boat has several significant effects, such as: (1) Reducing the number of migrants via; (2) Impact on the people smuggling business; (3) controversies and issues of human rights; and (4) Regional effects.